431 PICHIA OHMERI INFECTION IN A PEDIATRIC PATIENT: A CASE REPORT. Issue 1 (1st January 2007) - Ezeanolue, E. E.; Piggott, K.
Abstract : Introduction: Although commonly considered a contaminant, there is growing evidence that Pichia ohmeri is an opportunistic pathogen increasingly being reported as a rare cause of health care-associated infections in pediatric patients. Four pediatric cases have been reported in the literature, with one fatality. We report a case of Pichia ohmeri fungemia in a 5-month-old infant. Case Report: A 5-month-old Hispanic male with short gut syndrome and hepatic insufficiency was admitted to the pediatric unit with a day history of fever without other symptoms. Dependent on parenteral feedings for nutrition, he was discharged from the hospital 3 weeks earlier following a catheter-associated infection with vancomycin-resistant Enterococcus and Candida albican s. He was successfully treated for that infection with linezolid, fluconazole, and removal of the infected central venous catheter before a new Broviac catheter was placed. On this admission, his temperature was 104°F, respiratory rate 40/min, heart rate 156/min, and blood pressure 86/47 mm Hg. He was icteric and moderately dehydrated with significant hepatosplenomegaly. Examination of his other organ systems yielded no significant findings. Laboratory studies revealed a white blood cell count of 6, 500/mm 3 with 33% neutrophils, 63% lymphocytes, 2% monocytes; hemoglobin of 6.4 g/dL, and platelet count of 85, 000/mm 3 . His total bilirubin was 15.7 mg/dL; aspartate aminotransferase and alanine aminotransferase were 140 and 105 U/L, respectively. He was treated empirically with cefotaxime, linezolid, and fluconazole based on identification and susceptibility studies on previous organisms isolated from his blood. Six blood cultures obtained from both his central venous catheter and peripheral vein yielded Pichia ohmeri . Urine and cerebrospinal fluid cultures were sterile. Identification and susceptibility testing of Pichia ohmeri was performed using the Vitek closed system and database (bioMérieux, Inc., Durham, NC), and the isolate was determined to be susceptible to amphotericin B, fluconazole, voriconazole, and caspofungin. Due to persistent fever and positive blood cultures for Pichia ohmeri, the Broviac catheter was removed and his antifungal therapy was changed from fluconazole to amphotericin B deoxycholate, and he was treated for 10 days with repeat sterile cultures. Conclusion: This case adds to the growing reports of invasive infection with Pichia ohmeri species in pediatric patients. Clinicians need to be aware that although species in this genus were previously considered nonpathogenic, they should be considered to have the ability to cause clinically significant opportunistic mycoses.